2015
DOI: 10.1186/s12960-015-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of community health workers in Mozambique: a qualitative study of factors influencing motivation and programme implementation

Abstract: BackgroundCommunity health workers (CHWs) in Mozambique (known as Agentes Polivalentes Elementares (APEs)) are key actors in providing health services in rural communities. Supervision of CHWs has been shown to improve their work, although details of how it is implemented are scarce. In Mozambique, APE supervision structures and scope of work are clearly outlined in policy and rely on supervisors at the health facility of reference. The aim of this study was to understand how and which aspects of supervision i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 21 publications
2
115
0
1
Order By: Relevance
“…BRAC needs to provide adequate support to SS through regular supervision and monitoring of their responsibilities, to provide opportunities to rectify misunderstandings and enhance their skills. Supportive supervision often requires on the job training [44,45]. We also observed several constraints at the sub-district level of BRAC, including, a high dropout rate among supervisory-level staff members, staff members' concerns about salaries and benefits and coordination among the BRAC's programmes.…”
Section: Discussionmentioning
confidence: 77%
“…BRAC needs to provide adequate support to SS through regular supervision and monitoring of their responsibilities, to provide opportunities to rectify misunderstandings and enhance their skills. Supportive supervision often requires on the job training [44,45]. We also observed several constraints at the sub-district level of BRAC, including, a high dropout rate among supervisory-level staff members, staff members' concerns about salaries and benefits and coordination among the BRAC's programmes.…”
Section: Discussionmentioning
confidence: 77%
“…Although the policy holds priority for communities to select female volunteers, the majority of APEs is male. Large distances and irregularities in supervision represent important barriers for APEs to perform adequately (Ndima et al, 2015).…”
Section: Mozambiquementioning
confidence: 99%
“…Both the RHWs and the clients reported low engagement in health education programs, due to the less motivation to carry out the health education programs and the few demand needed for health information, respectively. The role of the management system in motivating community health workers has been demonstrated in numerous previous studies [18,19]. The findings of a study conducted in the north of Vietnam among health workers indicated that the motivation of RHWs was influenced by both financial and non-financial incentives, and one of the main motivating factors for them was appreciation by managers, colleagues and the community [20].…”
Section: Discussionmentioning
confidence: 89%